FINITE VOLUME METHOD AND CELL TRANSMISSION MODEL FOR TRAFFIC FLOW WITH JUNCTION - Zahra Kamalia, Putri
In this thesis, a macroscopic study on traffic flow model is considered using the LWR model, which is a 1D conservation equation. Relations between speed and density is assumed to follow Greenshield model. A road segment with a junction consisting of exit and entrance can be modeled using LWR model with the additional source/sink term. For the case of fixed entrance rate, Finite Volume Method and Cell Transmission Model are used to calculate the density and the results are compared with the existing analytical solution in order to test the validity of numerical scheme. After agreement is obtained, we present various simulation of traffic dynamics due to a exits-entrances from junction.